CryENGINE 3 SDK level design course - Floyd, Nick.; Safari eBooks ([S.l.] : Packt Pub., 2013)
"Are you a novice who wishes to get into game development, but have no experience or don't know where to start? Being an intermediate level designer, do you enjoy modifying your existing games and want to learn to move your skills up a notch? Then this course is meant for you! Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. The videos will explain everything that the viewer needs to know using a hands-on approach to follow along with. This course will also give the viewer the ability to take what they have learned and apply it to their own game level."--Resource description page.
Title from resource description page (viewed Oct. 15, 2013).
Presenter, Nick Floyd.
Keywords: Computer games -- Design; Computer games -- Programming; Electronic books